Baby steps to STEM : infant and toddler science, technology, engineering, and math activities - Barbre, Jean (St. Paul, MN : Redleaf Press, 2017)
'Innately curious, infants and toddlers love to explore, investigate, and discover-making the earliest years a perfect time to begin teaching the foundations of STEM. This book defines what science, technology, engineering, and math education looks like for this age group, and why it is so vital for children to develop STEM knowledge. Expand your understanding of STEM to lay the foundation for children to develop skills in critical thinking, communication, collaboration, and creativity. This book supplies fifty play-based developmentally appropriate activities for introducing STEM. All activities include extensions, inquiry questions, and tips on how to help parents strengthen children's learning at home. Jean Barbre, EdD, holds a master's degree in child and family studies from California State University Long Beach, a master's degree in counseling from California State University Fullerton, and a doctorate degree in educational leadership from Pepperdine University. She has more than thirty years of experience working with children and families in a variety of roles and currently teaches early childhood courses in community college and California State University system as well as presents at professional conferences across the country'--
'Jean Barbre's newest book offers rich, play-based, and developmentally appropriate STEM activities for the youngest of children--infants, toddlers, and twos. It also provides teachers with a strong basis of theory and practice in support of early childhood STEM education, instilling an awareness of the teachable STEM moments and suggesting a plethora of strategies, techniques, tips, and tools to lay the foundation for young children's twenty-first century STEM learning'--
How infants, toddlers, and twos learn -- The role of the caregiver -- Enhancing STEM learning in young children -- STEM activities.
Includes bibliographical references and index.
Keywords: Science -- Study and teaching (Early childhood) -- United States; Technology -- Study and teaching (Early childhood) -- United States; Engineering -- Study and teaching (Early childhood) -- United States; Mathematics -- Study and teaching (Early childhood) -- United States